The Development Of Green Homes In Malaysia : Assessing The Readiness Of Housing Development Company - Naintin, Peter Jr (2017)
Any business organisation want to upkeep their position in the diverse and dynamic market. For the housing development company, there are challenges from internal and external factors in developing green homes in Malaysia. This study is primarily to assess the acceptance on green homes development by the employees of the housing developer in Malaysia. The study used a structured survey, which was conducted independently to obtain feedback from respondents. In this study, 351 survey forms were distributed to respondents residing in major cities in Malaysia and a total of 105 completed questionnaires, which answered by respondents, were obtained.